Young black women’s narratives of “room-sharing” in university residences, Wits University - Sibanyoni, Tshiamo (My University, 2023)
In recent years, there has been an increase in the number of black students in South Africa who can now afford to attend university. As encouraging as this has been, there has been one great challenge in that there is now a significant need for accommodation, more than was needed during the apartheid era. Some universities, including the University of the Witwatersrand (popularly known as Wits University), attempted to resolve this by having first-year students share rooms and building and acquiring off-campus student accommodation. This study explored young black female students’ experiences of sharing a residence room at Wits University and how these experiences affect them daily. The results suggested that a positive relationship with one’s roommate made the transition to university and roomsharing much easier. The positive relationship further elicited a sense of belonging in the residence, whereas a negative relationship fostered a sense of exclusion. There were also links between a positive relationship with one’s roommate and benefits in academic performance. Class, different personalities (introversion versus extroversion), safety in residences, space negotiation and how management can improve were also explored. Key recommendations include equal allocation of resources and security for on-campus and off-campus residences, as well as an allowance to change one’s roommate in the face of unresolved and untenable conflict.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Community-Based Counselling Psychology to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Roommate friendships; Sense of belonging; Residence